The Role Of Education In Preserving Local Cultural Wisdom In Kapuas Hulu District - Endar Purnawan; Istiqomah; Ria Sabani (SOUTHEAST ASIA JOURNAL oF GRADUATE OF ISLAMIC BUSINESS AND ECONOMICS, 2023)
This article critically reviews the important role of education in preserving local wisdom and culture in Kapuas Hulu, West Kalimantan. Based on a thorough analysis of various literature reviews, the article presents an in-depth understanding of how the education system can become the backbone of efforts to preserve a rich and diverse cultural heritage. In this context, the study sheds light on strategies and concrete measures that can be adopted by educational institutions to strengthen the connection between the younger generation and their local cultural values. It was found that the integration of cultural values in the education curriculum, the organization of extracurricular activities that promote local culture, and the provision of in-depth knowledge about local traditions have a significant impact in fostering a sense of belonging and respect for cultural heritage. In addition, the results show that an educational approach that focuses on local wisdom can create a stronger connection between individuals and their cultural identity. Thus, overall, the findings of this study confirm the importance of cooperation between the worlds of education and culture in maintaining the continuity and relevance of Kapuas Hulu's culture in the ever-evolving era of globalization.